Internet Usage Behavior of the ICT Young Workforce in the Border Region - Moh Muttaqin (Jurnal Pekommas, 2019)
Indonesia became the sixth largest internet user country in 2014, and the country with the highest growth of internet users in 2016. At the end of 2018, internet users in Indonesia are categorized as heavy internet users, with more than 5GB data consumption per month only for internet connections via mobile devices. The question "what is the fast internet to use for?", Which was submitted by one of the Indonesian Minister of Communication and Information, should be an afterthought. UINSA Surabaya research states that internet use in Indonesia tends to be unproductive. This study aims to describe the behavior of internet access by user groups more specifically from previous research, namely the Information and Communication Technology (ICT) young workforce in the border region. By applying Uses and Gratification Theory (UGT), in addition to discussing user profiles of research subjects, the research also focuses on behavioral analysis with research objects in the form of a number of accounts, duration of access, access time, access devices and access needs. The study found that on average a user has 5.10 accounts on the internet for various purposes, most users access the internet for 2 to 4 hours per day (37.34%), most choose to access the internet at 20.01-00.0 (28.46%), generally accessing the internet using smartphones / cellular phones (68.86%), and dominant access is for entertainment/gaming purposes (33.88%).